Accident analysis on surabaya - gempol toll road - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Lingkungan Hidup,UGM, 1998)
ABSTRACT There are significant differences between ordinary road and toll road as a free way. By the term 'free', it does not mean that a toll road is entirely free from the problems of traffic accidents, even, the tendency for accident is higher in quality. This study identifies the main factors that cause an accident, vulnerable areas, and actions it have been carried out based on the characteristics of accidents. It aims to formulate alternatives of solutions in order to eliminate the contribution of the causes of accident. The characteristic of accidents on Surabaya â Gempol Toll Road shows a high rate of occurrence, in which driver take the highest responsibility followed by vehicles and road and environment. The road factor itself as the cause of accidents is almost unidentified. Among the various kinds of vehicle, minibuses are the most vulnerable ones to accident, and this indicates different trend from the past few years. There is an interrelationship among factors, and they are interacting to one another in causing an accident. An accident often happens due to driver's unpreparedness for the condition created by the toll road. Actions to eliminate accident should be adjusted to the existing characteristics. Single sites management (by the installment of sign post, wingspan, etc) and mass action management (safety campaign and assistance, etc.) are among the recommended actions to take.